The effect of blood flow rate on dialysis recovery time in patients undergoing maintenance hemodialysis: A prospective, parallel‐group, randomized controlled trial. Issue 2 (4th March 2019) - Duggal, Vishal; Hussein, Wael F.; Reiterman, Marc; Sun, Sumi J.; Abra, Graham E.; Schiller, Brigitte
Abstract: Introduction : A majority of patients with end‐stage renal disease (ESRD) on in‐center hemodialysis (HD) require several hours to recover from an HD session. Patients and caregivers identify fatigue as a high priority for improvement. However, evidence for practical interventions to improve recovery time from conventional in‐center HD is lacking. The effect of blood flow rate reduction on dialysis recovery time (DRT) is unknown. Methods : Multicenter, single‐blinded, randomized, parallel‐design controlled trial of blood flow rate reduction vs. usual care. One‐hundred two patients with ESRD undergoing maintenance HD in 18 centers with baseline DRT of greater than 6 hours were included as subjects. The intervention was a blood flow rate reduction of 100 mL/min, to a minimum of 300 mL/min. The primary outcome was the between‐group difference in change in DRT. Secondary outcomes were changes in London Evaluation of Illness (LEVIL) survey responses from baseline. Findings : Baseline median DRT was 720 (IQR 360–1013) minutes in controls and 720 (IQR 360–1106) minutes in the intervention group. DRT decreased in both groups. Mean change from baseline (95% confidence interval) at Week 4 in the study was −324 (−473, −175) minutes in the control group and −120 (−329, 90) minutes in the intervention group. The change from baseline was more profound in the control group (P = 0.05). Secondary outcomes of measures of quality of life reported on the LEVIL survey showed more improvement in patients' feelings of general well‐being in the control group (P = 0.01). Differences between groups in pain, feeling washed out or drained, sleep quality, shortness of breath, and appetite were not statistically significant. Discussion : Blood flow rate reduction did not improve DRT over usual care. Though more work needs to be done to address patient‐reported fatigue, a significant positive impact may not be achieved without substantial changes in dialysis prescription.